Content Analysis of Newspaper Framing of Chief Minister of Karnataka (Journal of Advanced Research in Journalism & Mass Communication, 2018)
A newspaper is a powerful tool that has the potential to not only inform but create public opinion on an issue, person, or political movement. There are many past examples of the effect of newspaper coverage of politics on the outcome of elections. Every media organization would have its political leanings, and such leanings act as a selection criterion in portraying an individual, opinion leader, or a political aspirant. This study is intended to see if the ideology of the newspaper has a relationship with the coverage given to political parties and leaders. The study would compare, using content analysis and framing theory, the coverage of the CM in an English newspaper, The Times of India, and a Kannada newspaper, Prajavani, to see if there is any bias that can be due to the political ideology of the two newspapers. How to cite this article: Shantharaju S, Naresh Rao H.Content Analysis of Newspaper Framing of Chief Minister of Karnataka. J Adv Res Jour Mass Comm 2018; 5(3): 1-7.